2020
DOI: 10.4018/978-1-7998-6664-0.ch001
|View full text |Cite
|
Sign up to set email alerts
|

High-Impact Writing Support for Online Students Writing a Dissertation in Practice

Abstract: This chapter examines the unique writing needs of professional doctoral students and the writing goals of the dissertation in practice that distinguish these students from traditional research-oriented graduate student writers. In this chapter, the authors survey emerging scholarship that establishes best practices for online writing support. Additionally, this chapter combines the insights gained from the discussion of professional doctoral students' unique needs and writing support research in order to estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Garcia & Yao (2019) explored the utility of an online seminar to prepare students for scholarly work at the doctoral level. Werse, Lively, & Crocker Papadakis (2021) found that high-impact support in the area of writing had a positive impact on the dissertation outcomes of online doctoral students. Key parameters influencing student outcomes center around student factors, faculty factors and peer-mentoring.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Garcia & Yao (2019) explored the utility of an online seminar to prepare students for scholarly work at the doctoral level. Werse, Lively, & Crocker Papadakis (2021) found that high-impact support in the area of writing had a positive impact on the dissertation outcomes of online doctoral students. Key parameters influencing student outcomes center around student factors, faculty factors and peer-mentoring.…”
Section: Literature Reviewmentioning
confidence: 96%